The Language Environment of Santri at Salaf Islamic Boarding School in Cirebon - Uctuvia, Vina; Jaza, Zimam Farid Hadi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
This research delves into the linguistic intricacies within the Salafi Islamic boarding school situated in Babakan, Ciwaringin, Cirebon—a microcosm of diversity in social and linguistic backgrounds. Employing a descriptive qualitative design with a sociolinguistic approach, the study explores language maintenance and shift among the students, emphasizing the intricate interplay between language and social contexts. Through the Simak Bebas Libat Cakap 'observation' technique, questionnaires, and interviews, the data unveils a dynamic coexistence of language maintenance and shift, notably observed in Bahasa Cirebon, Indonesian, and regional languages. Native speakers exhibit resilience in using Bahasa Cirebon during interactions with diverse interlocutors, while language shift occurs when individuals with distinct linguistic backgrounds opt for languages other than the regional one in communicative events. This research not only provides insights into linguistic resilience within the Salafi pesantren community but also highlights the adaptability of regional languages in multifaceted linguistic environments. The incorporation of the Unified Regional Linguistic Resilience Theory enriches the theoretical underpinning, offering a comprehensive lens for comprehending language dynamics in Islamic boarding schools. This contribution extends to the broader discourse on language, identity, and communication, emphasizing the significance of regional languages in diverse sociocultural settings.